2007
DOI: 10.1007/s10522-007-9116-4
|View full text |Cite
|
Sign up to set email alerts
|

Lack of replication of genetic associations with human longevity

Abstract: The exceptional longevity of centenarians is due in part to inherited genetic factors, as deduced from data that show that first degree relatives of centenarians live longer and have reduced overall mortality. In recent years, a number of groups have performed genetic association studies on long-living individuals (LLI) and young controls to identify alleles that are either positively or negatively selected in the centenarian population as consequence of a demographic pressure. Many of the reported studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 25 publications
0
54
1
Order By: Relevance
“…Finally, we examined three genes not belonging to any of these biological processes but still considered reliable candidates in previous studies: the highly discussed candidate gene angiotensin I-converting enzyme (ACE), for which the I/D insertion/deletion (tagged by rs4343 (Abdollahi et al 2008)) has been reported by several authors to be associated with longevity (Arias-Vasquez et al 2005;Cellini et al 2005;Frederiksen et al 2003;Luft 1999;Novelli et al 2008;Schachter et al 1994;Zajc et al 2012); the iron absorption regulatory protein hfe, for which the Cys282Tyr variation (rs1800562) was found to decrease with age Lio et al 2002); and, finally, MTHFR, which is of importance for the essential remethylation of homocysteine to methionine, where the C677T (rs1801133) polymorphism has been suggested as associated with longevity (Stessman et al 2005;Todesco et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we examined three genes not belonging to any of these biological processes but still considered reliable candidates in previous studies: the highly discussed candidate gene angiotensin I-converting enzyme (ACE), for which the I/D insertion/deletion (tagged by rs4343 (Abdollahi et al 2008)) has been reported by several authors to be associated with longevity (Arias-Vasquez et al 2005;Cellini et al 2005;Frederiksen et al 2003;Luft 1999;Novelli et al 2008;Schachter et al 1994;Zajc et al 2012); the iron absorption regulatory protein hfe, for which the Cys282Tyr variation (rs1800562) was found to decrease with age Lio et al 2002); and, finally, MTHFR, which is of importance for the essential remethylation of homocysteine to methionine, where the C677T (rs1801133) polymorphism has been suggested as associated with longevity (Stessman et al 2005;Todesco et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These studies include rs2542052 in APOC3 (Novelli et al 2008), rs5882 in CETP (Cellini et al 2005;Novelli et al 2008), I/D insertion/deletion in ACE (Agerholm-Larsen et al 1997;Bladbjerg et al 1999;Blanche et al 2001;Yang et al 2009), rs1800562 in HFE (Carru et al 2003;Coppin et al 2003), and rs180113 in MTHFR (Bladbjerg et al 1999;Khabour et al 2009;Hessner et al 2001;Brattstrom et al 1998) and−176C/G in IL6 (Pes et al 2004;Wang et al 2001). Furthermore, a few meta-analyses or pooled analyses have been published; for APOE ε4 and the ACE I/D, insertion/deletion association was supported (McKay et al 2011;Zajc et al 2012), while for the IL6 −176C/G polymorphism, a North/South European gradient of association was suggested (Di Bona et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Novelli et al ( 18 ) eventually tested the relationship between longevity and the presence of this SNP (among other candidate SNPs) in a cohort of elderly American Caucasians but, in this case, this APOC3 SNP was not over-represented. Our study did not fi nd any difference in the AUC of the various lipid fractions during lipemia, but a different kinetics, as the times to maximum peak of TG and large TRL-TG were delayed in subjects homozygous for the minor allele (AA).…”
Section: Discussionmentioning
confidence: 99%
“…The three SNPs analyzed here were also previously studied: APOC3 -2886T/G, reported as Ϫ 2854T/G, has been associated with altered fasting triglycerides ( 17 ). APOC3 -640, rs2542052, has been described as Ϫ 641C/A and associated with longevity and HDL levels ( 18,19 ), although other authors did not replicate the fi ndings ( 18 ). The minor allele of the APOC3 synonymous G34G variant (rs4520, also known as 1100C>T) has been widely studied, fi rst reported to associate with elevated triglyceride levels ( 20 ).…”
Section: Subjectsmentioning
confidence: 91%
“…32,33 Although polymorphisms in more than 80 genes have been reported which are associated with human longevity in various populations internationally, no reproducible association, except for the apolipoprotein-E gene involved in the cholesterol metabolism, has been found across the globe. 29,34 Some other genes whose allelic variations have been shown to associate with long life span are components of the immune system and the human leukocyte antigen region. These include the human leukocyte antigen haplotypes, mitochondrial haplotypes, inflammation pathway genes and cytokines.…”
Section: Overexpression Of Some Genes Increases Life Span In Model Symentioning
confidence: 99%